2018
DOI: 10.1186/s12966-018-0697-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity to improve cognition in older adults: can physical activity programs enriched with cognitive challenges enhance the effects? A systematic review and meta-analysis

Abstract: BackgroundAging-related cognitive decline and cognitive impairment greatly impacts older adults’ daily life. The worldwide ageing of the population and associated wave of dementia urgently calls for prevention strategies to reduce the risk of cognitive decline. Physical activity (PA) is known to improve cognitive function at older age through processes of neuroplasticity. Yet, emerging studies suggest that larger cognitive gains may be induced when PA interventions are combined with cognitive activity (CA). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
191
4
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(229 citation statements)
references
References 75 publications
(104 reference statements)
9
191
4
10
Order By: Relevance
“…Previous meta‐analyses mostly focused on one type of mind‐body exercise, such as tai chi, yoga, or dance, for cognitive functions . Other reviews explored physical exercise including aerobic, resistance exercise, tai chi, or yoga for preventing and addressing cognitive impairment in older adults . Although these reviews involved mind‐body exercise as a component, the studies mainly focused on aerobic and resistance exercise, which might increase the confounding factors and cannot comprehensively and accurately assess the effect of mind‐body exercises on cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta‐analyses mostly focused on one type of mind‐body exercise, such as tai chi, yoga, or dance, for cognitive functions . Other reviews explored physical exercise including aerobic, resistance exercise, tai chi, or yoga for preventing and addressing cognitive impairment in older adults . Although these reviews involved mind‐body exercise as a component, the studies mainly focused on aerobic and resistance exercise, which might increase the confounding factors and cannot comprehensively and accurately assess the effect of mind‐body exercises on cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]51 Other reviews explored physical exercise including aerobic, resistance exercise, tai chi, or yoga for preventing and addressing cognitive impairment in older adults. [52][53][54] Although these reviews involved mind-body exercise as a component, the studies mainly focused on aerobic and resistance exercise, which might increase the confounding factors and cannot comprehensively and accurately assess the effect of mind-body exercises on cognitive functions. Therefore, our study paid more attention to the overall effects of mind-body exercise and comprehensively evaluated cognitive performance on cognitive intact and cognitive impairment in older adults, which was different from what was found in previous studies.…”
Section: Findings In Relation To Previous Reviewsmentioning
confidence: 99%
“…At least two systematic reviews state that physical activity is one of the seven modifiable risk factors for cognitive impairment in the elderly [5,8]. Evidence-based studies show that physical activity and sedentary behaviour play an important role in cognitive function in older adults [9]. However, some studies have reported associations between physical activity and cognition cross-sectionally [10,11] and longitudinally [12].…”
mentioning
confidence: 99%
“…Longitudinal studies suggest older sedentary adults who maintain an exercise program for at least 6 months perform better on measures on processing speed, executive function, and memory . A meta‐analysis by Gheysen et al found that physical activity combined with cognitive activities resulted in significantly larger gains in cognition as compared to physical activity alone, suggesting a combination of physical activity and cognitive exercises are perhaps the most effective modality for preventing cognitive decline in older adults …”
Section: Improving Cognition With Exercise and Physical Activitymentioning
confidence: 99%